Extending legal professional privilege to non-legal tax practitioners in South Africa: a comparative and constitutional perspective - Jani, Pride (Rhodes University, Faculty of Commerce, Department of Accounting, 2011)
This study explains the differing rights of taxpayers, based on the nature of the profession of the tax adviser they consult. Those who utilize the services of tax attorneys can rely on the protection afforded by legal professional privilege whereas those who obtain their advice from non-legal advisers, such as accountants and other tax advisers, cannot claim the same protection. Legal professional privilege is a substantive right which should be extended to cover clients of non-legal tax advisers. The continued denial of the privilege to clients of nonlegal tax practitioners while it is availed to those who approach legal practitioners infringes the rights to privacy and equality contained in the South African Constitution. The object of this research is to show that the common law concept of legal professional privilege is amenable to extension so as to cover the clients of non-legal tax advisers. A qualitative approach was adopted which involved an in-depth analysis of the origins, rationale as well as the requirements for the operation of the doctrine. This also involved a constitutional as well as a comparative dimension. The constitutional dimension sought to show that the current distinction is untenable under the South African Constitution by virtue of the infringement of the rights to privacy and equality. The comparative dimension presented an analysis of the various jurisdictions that have extended the doctrine as well as those that are still to do so or have adamantly rejected the idea. The differential treatment of taxpayers based on the professional they engage contravenes the privacy and equality provisions and is thus unconstitutional. The study demonstrates that legal professional privilege is amenable to extension and there is need for legislative intervention as the courts are limited in the extent to which they may intervene in light of the separation of powers and judicial deference. Legal professional privilege should therefore be extended to protect the clients of non-legal tax advisers as opposed to partial protection which subsists at the moment.
Keywords: Uncatalogued